Bibliometric Study : Rainfall Classification - Prediction using Machine Learning Methods - Riza, Ozzy Secio; Nuryadi, Ari (Publisher: Fakultas Ilmu Komputer, Institution: Universitas Lancang Kuning, 2023)
This Research aims to review the machine learning methods used for classifying or predicting rainfall, using various features from existing data. The study used a bibliometric approach to search for metadata related to rainfall classification and prediction studies using machine learning keywords in Scopus journals. There found 94 metadata articles stored in a Comma Separated Values (CSV) file. The data in this article used published articles from 2014 to 2023 with relevant topics. The study provides information on the latest machine learning methods used for classifying or predicting rainfall. The findings of the study include an increase in published articles by 221.43% from 2018 to 2022. The article titled